THE PROPHETIC MODEL OF CHARACTER EDUCATION: AN ANALYSIS OF EDUCATIONAL VALUES IN THE SUNNAH - Maslani Maslani; Fazrin Syaibatul Hamdi Muzami; Akin Mustakin; Mungkassifurahman Mungkassifurahman; Evi Luthfi Nurulhayati; Alfa Rohmatin (LP2M IAI Al-Khairat Pamekasan, 2026)
This study examines the role of the Prophet Muhammad’s hadith and sunnah as the foundation of Islamic character education. Using a qualitative library research method, this paper analyzes classical and contemporary literature related to moral values derived from prophetic traditions. The study emphasizes that Islamic education aims not only to develop intellectual capacity but also to shape moral integrity, spiritual maturity, and social responsibility. The findings reveal that the prophetic model of education integrates several key principles: exemplary behavior (uswah hasanah), compassion and empathy, consistent moral habituation, appreciation of knowledge, discipline, and the balance between worldly and spiritual life. These values provide a holistic framework for addressing the moral and ethical crises faced by modern society. The research concludes that revitalizing prophetic values within formal and non-formal education can produce a generation of Muslims who are intellectually competent, emotionally resilient, and spiritually grounded. Therefore, the hadith and sunnah are not merely historical or theological references but serve as a living civilizational strategy for character formation in the contemporary era.